(untitled) (Homoeopathy for All, 2024)
The cutaneous clinical manifestation characterized by deep dermatitis with granulomatous reaction, appearance of an edematous, circular and alopecic nodule was found abruptly in a 6-year-old female canine patient. Diagnosed with Lupus Erythematosus due to the presence of major symptoms, the causes of kerion were excluded by the species Microsporum canis, M. gypseum and Trichophyton mentagrophytes, which were found to be absent in the cytology, fungal and bacterial cultures of the present case. Using Causticum 30 cH, three globules, twice a day, the patient’s inflammatory process ceased on the third day, turning the lesion into a wound that healed on the fifteenth day. Complete rehairing of the affected area was observed on the thirtieth day. Immunological parameters that affected skin morphometry in the initial phase, showed positive results after the use of homeopathy, reflecting the magnitude of the therapy adopted in dermatopathies.